Wide excision and healing by secondary intent for the surgical treatment of hidradenitis suppurativa: A single-center experience. Issue 4 (April 2016) - Humphries, Laura S.; Kueberuwa, Essie; Beederman, Maureen; Gottlieb, Lawrence J.
Summary: Background: This study reviewed a single center's 14-year experience with surgical treatment of chronic, severe hidradenitis suppurativa (HS) through wide excision technique and healing by secondary intention. Methods: All patients who underwent wide excision of HS between 2000 and 2014 and allowed to heal by secondary intention were included. Wound care consisted of topical antimicrobials and hydrotherapy. Physical therapy was initiated for joint contracture prevention. Patients were followed until complete wound closure. Results: Seventeen patients underwent 23 separate surgical encounters, five with excision of multiple areas. Seventeen excisional procedures were conducted on the upper half of the body (axillary, breast) and 11 on the lower half (inguinal, perineum, perianus, and abdomen). Two patients developed HS recurrence adjacent to the surgical site (one requiring reexcision and the other treated with topical therapy), whereas two developed HS flares at distant nonsurgical sites managed medically. The mean follow-up was 1.02 years with a median of 6 months ranging from 1.2 months to 5.25 years. Complete wound healing ranged from 8 weeks to 16 months, with limited range of motion (ROM) in two patients. Conclusions: Attempts at removing all tissue affected by HS through wide surgical excision are the mainstay intervention for achieving complete local cure, particularly in the most severe cases of the disease. Our experience with wide excision of disease and healing by secondary intent demonstrated clinically satisfactory functional and excellent aesthetic results in multiple anatomic areas and even for large defects. This healing modality requires strict adherence to the wound healing protocol, which is often tolerated only by patients who have endured symptoms of severe HS for an extended length of time.